Correlation of muscular strength and balance in relation to single leg squat analysis in male football players – an observational study - Patil, Mrugnayani Chandrashekhar; Babu, Sarath (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Individual participation in sports with inadequate preparation, especially during competition, results in an increased incidence of injury. Athletes commonly suﬀer from lower extremity musculoskeletal pain. During growth, several biomechanical factors contribute to muscular imbalance, which results in injury. The aim of the current study was to determine the correlation between lower extremity strength and balance in relation to single leg squat depth.Methods. A total of 100 male football players were included in the study. Lower extremity qualitative and quantitative squat analy-ses were performed for both legs. Isometric strength and balance for the lower extremities were assessed via a dynamometer and the Y balance test, respectively.Results. There is a moderate correlation between the visual squat performance and the strength of the hip extensor in the dominant leg and the hip abductors in the non-dominant leg. A moderate correlation of the maximum squat depth was found with the hip abductors, hip extensor, and knee ﬂexor on the dominant side. The p value was < 0.05 and the r value was between 0.50 and 0.70, which was considered signiﬁcant.Conclusions. Strength and balance both inﬂuence squat performance. Balance has a stronger inﬂuence than strength in single leg squat performance.
Keywords: dominant leg; non-dominant leg; single leg squat